The economic impacts of terrorist attacks - Richardson, Harry Ward; Gordon, Peter 1943-; Moore, James Elliott (Edward Elgar Pub., 2005)
Using a variety of methodologies and original research, the authors of this study consider different types of terrorist attack on public utilities. They suggest that a greater understanding of the economic costs of terrorist attacks can be used to focus investment on prevention and response.